Relationship between implementation of cooperative vocational education and job offering among apprentice of national dual training system in Malaysia. - Saari, Hazril Azmin; Mat Rashid, Abdullah (IDOSI Publications, 2013)
The objective of this research is to examine a relationship between implementation of cooperative vocational education and job offering among apprentice of national dual training system in Malaysia. Furthermore, the study also identifies several factors to predict job offering to the respondent. The total respondent of the study are 285 apprentices which enrolled for Malaysian Skills Certificate Level 2 at various types of programs and companies that offer national dual training system. These respondents were selected through stratified random sampling based on location of training institutions. Data was analyzed by frequency and percentage for descriptive statistics and logistic regression for inferential statistics. The result shows MNC and GLC companies’ offers block release training mode meanwhile SME companies’ offers day release training mode. The result shows that the three combination independent variables significantly predict getting a job offer. However, only type of company and training mode are significantly contributing to the prediction. Further chi square analysis results indicate that getting a job offer are significantly different in regards respondent program of study, training mode and type of company they attached during the SLDN program.